ANALISIS KUALITAS PELAYANAN PUBLIK DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA DUMAI - Sukmaida Sukmaida; Eka Komalasari (UIR Press, 2018)
Dumai is a small hamlet on the seashore of the eastern province of Riau. Dumai is a result of the expansion of Bengkalis. Inaugurated as the City on 20 April 1999 by Law No. 16 of 1999 which was the previous status of the City of Dumai. Dumai City is a city in the province of Riau, which has a population of 271 523 which consists of 7 districts and a total area of 1623.38 km2. This study aims to determine the quality of public services in the Department of Population and Civil Registration Dumai City. With this type of research is Desckriptif Survey illustrates the true state with the Kota Dumai study sites sampled and that society has an interest relating to the management of administration, and government officials / employees of the Department of Population and Civil Registration Dumai City with data collection mnggunakan interview and questionnaire . The conclusions of this study are, when viewed from some ministry, the public will tend to have easy, fair and equitable, but in practice that is particularly dumai city in quality of public services as a benchmark for service delivery tends to existing provisions. Maintenance process is convoluted and time consuming reality that must be traveled by the public. Based on the results of this study through questionnaires and interviews the observation of researchers is the lack of quality of public services in providing services, this is caused by the low performance of the pegawaidalam serve and did not escape the political conditions of the employees.